Epratuzumab and Blinatumomab as Therapeutic Antibodies for Treatment of Pediatric Acute Lymphoblastic Leukemia: Current Status and Future Perspectives. - Franca, Raffaella; Favretto, Diego; Granzotto, Marilena; Decorti, Giuliana; Rabusin, Marco; Stocco, Gabriele (Curr Med Chem, 2017)
BACKGROUND: More than 85% of children affected by acute lymphoblastic leukemia (ALL) are successfully treated; however relapse remains a remarkable clinical concern, with 50-60% of relapsing patients facing a fatal outcome. Management of relapsed patients includes standardized intensive risk-adapted regimens based on conventional drugs, and hematopoietic stem cells transplantation for patients with unfavourable features. Biological drugs, in particular the monoclonal antibody epratuzumab and the bi-functional recombinant single chain peptide blinatumomab, have been recently recognized as novel potential agents to be integrated in salvage ALL therapy to further improve rescue outcome. METHODS: A systematic search of peer-reviewed scientific literature and clinical trials in public databases has been carried out. Both clinical and pre-clinical studies have been included to summarize recent evidence on epratuzumab and blinatumomab for salvage ALL therapy. RESULTS: Sixty-two papers and 25 clinical trials were included. Although not all patients responded properly to these agents, their use in relapsed and refractory pediatric ALL seems promising. CONCLUSION: Phase 3 studies have recently begun and more consistent results about epratuzumab and blinatumomab safety and efficacy in comparison to conventional therapies are expected in the next years. Epratuzumab seems safe in the dosing scheme proposed in ALL, but its efficacy over the conventional chemotherapy is still questionable. Blinatumomab has shown promising results in high risk cases such as elder adult patients and conclusive studies on pediatric ALL are needed. Patient inter-individual variability to these agents has not been investigated in depth, but this issue needs to be addressed, in particular for blinatumomab.
Keywords: Antibodies, Bispecific; Antibodies, Monoclonal; Antibodies, Monoclonal, Humanized; Antineoplastic Agents; Child; Clinical Trials as Topic; Half-Life; Humans; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Sialic Acid Binding Ig-like Lectin 2